Novel Use of Single Phase Electromechanical Energy Meter for Standardized Testing of Digital Energy Meters (International Journal of Engineering and Computer Science, 2014)
To ensure reliability and high accuracy testing of energy meters has been imperative. The conventional testing of digital energy meters poses some drawbacks viz. slow process, power loss and requirements of resistor and capacitor banks. This paper proposes the modified single phase energy meter, making it standard for the testing of Digital Energy Meters. For the purpose 72 holes are drilled on the disc of electromechanical energy meter and then recalibration of the same is done before using it as “standard”. The holes on the disc shall be detected by the sensor which is connected with the microcontroller which counts the pulses obtained. The number of pulses obtained from electromechanical meter and Digital Energy meter are compared to gauge the error in Digital Meter.